2006
DOI: 10.1177/0739986305283221
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Health Among Adult Women of Mexican Origin

Abstract: Self-rated health (SRH), a consistent predictor of mortality among diverse populations, is sensitive to health indicators and social factors. American-born Hispanics report better SRH than their foreign-born counterparts but simultaneously report poorer health indicators and have shorter life expectancy. Using a matched prospective cross-sectional design, we analyzed data from 631 agematched pairs of women, born in the United States or Mexico, enrolled in a cohort study based in Houston, Texas. Our first goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
(45 reference statements)
0
8
0
Order By: Relevance
“…Several studies suggest that with increased time in the United States, there are increased levels of depression among women of Mexican origin (Crockett et al, 2007;Hiott, et al, 2006;Wilkinson et al, 2006). Additionally, separation from family is a significant stressor that may contribute to depression among Mexican and Mexican American women residing in the United States.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Several studies suggest that with increased time in the United States, there are increased levels of depression among women of Mexican origin (Crockett et al, 2007;Hiott, et al, 2006;Wilkinson et al, 2006). Additionally, separation from family is a significant stressor that may contribute to depression among Mexican and Mexican American women residing in the United States.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Several studies have suggested that mental health grows worse with increased acculturation (Crockett et al, 2007;Heilemann et al, 2002;Hiott et al, 2006;Wilkinson et al, 2006). For example, among Mexican women residing in the southeast United States for less than 5 years, one quantitative descriptive study of 150 recent immigrants from Mexico found that decline in mental health was associated with more time spent in the United States (Hiott et al, 2006).…”
Section: Acculturationmentioning
confidence: 99%
“…However, several factors related to self-rated health such as physical activity, psychosociological conditions, education, and personal health practices were not considered. 29 Adults with poorer perceptions of their health may be less engaged in preventive health practices or self-care that contributes to better health. Other studies have reported an association between exercise participation and self-rated health: people who do not participate in exercise on a regular basis are more likely to evaluate their health as poor.…”
mentioning
confidence: 99%